Implementasi Sistem Pengendalian Inventory pada UMKM Warung Awi Makanan Khas Selatpanjang - Hery Haryanto; Winston Winston (Lembaga Pengembangan Kinerja Dosen, 2024)
Warung Awi is a micro, small, and medium enterprise (MSME) that has been operating since 2009 and has become one of the leading culinary destinations in Batam City. However, the business has encountered various challenges, particularly in managing raw material inventory. Therefore, it is crucial for Warung Awi to adopt a more effective and efficient inventory management system. One approach to address this issue is by implementing the Economic Order Quantity (EOQ) and Reorder Point (ROP) methods. Data collection was conducted using both primary and secondary methods, including transaction records and interviews with the business owner. The results of this study produced a web-based system that assists the owner in managing inventory. The implementation of this system received positive feedback from the owner, as it significantly improved efficiency in inventory recording and management.